Development of an Application for Calculating the Power Flow of Bipolar DC Networks Using the MATLAB Environment (2024)
This work proposes the design of a graphic interface to solve the power flow problem in unbalanced bipolar direct current (DC) networks using the successive approximations method. The goal of the graphic interface is to facilitate the user's calculation of the power flow without the need for prior knowledge of programming languages. This work is divided into three stages. The first presents the mathematical power flow model for unbalanced bipolar DC networks using the successive approximations method. The second presents the implementation of the graphic interface, applying the aforementioned mathematical model. The third stage presents the main characteristics of the DC systems under study, in addition to solving the power flow problem through the program and a comparison with the results reported in the specialized literature. Numerical validations demonstrate that the program solves the power flow and finds the same solution as the specialized literature with 100% efficiency, which confirms the program's accuracy and establishes it as a reliable source of information. This document shows the step-by-step creation of the interface, which was tested with two types of networks to corroborate the validity of the program.